Building Your Business with Google for Dummies - Hill, Brad (Wiley Publishing, 2011)
The first-ever book to show businesses step by step how to capitalize on advertising programs offered by Google, the world's #1 search engine, with more than 200 million search queries per day Written by a veteran For Dummies author working in cooperation with Google, which will help support the book From selecting the right keywords to crafting the right message, the book explains how to boost site traffic using AdWords, Google's hugely successful sponsored-link advertising program, which now has more than 150,000 advertisers Also details how to make money with AdSense, a Google program that funnels relevant AdWords ads to other sites-and pays those sites whenever someone clicks on them